The Degree of Islamic Studies Teachers' Use of Constructivist Theory Principles in Teaching Situations - Al-Malki, Ali Atiyah Ali (Journal of Curriculum and Teaching Methodology, 2025)
The aim of the study was to explore the degree to which Islamic studies teachers use the principles of constructivist theory in teaching situations, and to investigate whether there are statistically significant differences in the mean scores of the teachers' use of these principles based on variables such as qualification, educational stage, and years of experience. To achieve the study's objectives, the researcher employed a descriptive survey method, surveying the opinions of 306 Islamic studies teachers in the General Education Department of the Makkah region in Saudi Arabia. A questionnaire was used as the data collection tool. The study concluded with several findings, the most significant being that the mean scores for the use of constructivist theory principles by Islamic studies teachers in teaching situations were very high, with an average score of 4.17. There were no statistically significant differences in the mean scores of Islamic studies teachers' use of constructivist principles based on the variables of qualification and years of experience. However, statistically significant differences were found based on the educational stage, with the mean score for primary school teachers (4.30) being higher than that of middle school teachers (3.96), with the difference favoring the primary school teachers.
Keywords: Islamic Studies Teachers; Principles of Constructivist Theory; Teaching situations